If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5g + 3(-7 + 2g) = 1 + -1g 5g + (-7 * 3 + 2g * 3) = 1 + -1g 5g + (-21 + 6g) = 1 + -1g Reorder the terms: -21 + 5g + 6g = 1 + -1g Combine like terms: 5g + 6g = 11g -21 + 11g = 1 + -1g Solving -21 + 11g = 1 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. -21 + 11g + g = 1 + -1g + g Combine like terms: 11g + g = 12g -21 + 12g = 1 + -1g + g Combine like terms: -1g + g = 0 -21 + 12g = 1 + 0 -21 + 12g = 1 Add '21' to each side of the equation. -21 + 21 + 12g = 1 + 21 Combine like terms: -21 + 21 = 0 0 + 12g = 1 + 21 12g = 1 + 21 Combine like terms: 1 + 21 = 22 12g = 22 Divide each side by '12'. g = 1.833333333 Simplifying g = 1.833333333
| 2x^2+10x=7x+2 | | 9-.2(v-8)=.3(6v-8) | | -18x-6x=-5 | | 5x-15x=70 | | -x+12x=-33 | | 4x^2-67x-289=0 | | .08(15)+.4x=.05(36+7x) | | bz+cz+bx+cx= | | 5x-7=23+3x | | -14x=-182 | | -x/4=-6 | | 15=-d+30 | | (3q+2)(9q^2-12q+4)= | | 4a+-3b= | | .3(a-18)=.9a | | x/4=-6 | | 3x+5x+3+4=39 | | ln(4+x^2)=ln(x)+2ln(2) | | 6a-b-2a-2b= | | .2+1.3t-.8t=1-2.1t-.8 | | -1-2x=-15 | | 13x+15=6x+183 | | 3d=36 | | 8z-22=3(3z-11)-z | | -7x-13=57 | | 13x-15=6x+183 | | -3-4x=-7 | | 54=a-25 | | 49-3x=6x+17 | | 2x-(x+2)+3(x-5)=(x+2)+15 | | 4x-10=-42 | | 1+8x-x^2=0 |